A magic spark - Young, Jessica (Jessica E.); Vanderbemden, Marie (New York, NY : Scholastic Inc., 2020)
Ruby, Iris, and Pip first met on their first day of fairy school, and they immediately became best friends, testing their wings, and enjoying their magical adventures--but sometimes it takes a little time for a fairy to find her true magic spark.
1.9.
K-3.
410L
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Best friends -- Juvenile fiction; Fairies -- Fiction; Magic -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Fantasy; Fantasy fiction; Readers (Elementary)